1996
DOI: 10.1021/ma951432a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Optical Properties of Poly{(4-nitrophenyl)-[3-[N-[2-(methacryloyloxy)ethyl]- carbazolyl]]diazene}

Abstract: Poly{(4-nitrophenyl)-3-[N-[2-(methacryloyloxy)ethyl]carbazolyl]]diazene} was prepared and its photoinduced birefringence, diffraction grating, and photorefractive asymmetric two-beam gain coupling were studied. The monomer was obtained by performing azo coupling in a two-phase water−dichloromethane system in the presence of a phase transfer catalyst. Photoinduced birefringence of up to 0.09 was observed and diffraction efficiencies of up to 25% were obtained, with atomic force microscopy studies revealing that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
109
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 160 publications
(109 citation statements)
references
References 32 publications
0
109
0
Order By: Relevance
“…The lines are drawn to guide the eye. [4,10,24,35], copolymers [5,10,17,36,37] and blends [38,39] with the advantage of a relatively small writing time. The comparison of the two mixtures indicated that 41% molar fraction of azopolymer are sufficient for the photoinduced birefringence, with an optimized writing process using 1.4 mW of laser power.…”
Section: Tablementioning
confidence: 99%
“…The lines are drawn to guide the eye. [4,10,24,35], copolymers [5,10,17,36,37] and blends [38,39] with the advantage of a relatively small writing time. The comparison of the two mixtures indicated that 41% molar fraction of azopolymer are sufficient for the photoinduced birefringence, with an optimized writing process using 1.4 mW of laser power.…”
Section: Tablementioning
confidence: 99%
“…This procedure was reported previously as giving good yields for the functionalization of the well-known less-reactive carbazole derivatives. [18][19][20] Our earlier attempts to obtain the molecules with different chromophore loading by varying the molar ratio of carbazoles to diazonium salt failed probably because of the bulkiness of the introduced nitrophenyl group and the steric effect of the coupling produced. Only two products, M1 and M2, were attained with different yields under the same reaction time (24 h) and temperature (room temperature) no matter what the ratio of diazonium salt was.…”
Section: Design and Synthesis Of Molecular Glassmentioning
confidence: 99%
“…In previous reports, thin films of single-component carbazole-based polymers containing the same chromophore as in M1 and M2 were found to be suitable materials for storage of a photorefractive grating, [18,19,4,26] which suggests that the azocarbazole group could, in principle, be trifunctional, that is, act as a photosensitizer for charge generation, a charge transporting agent, and an EO moiety. The initial attempt to obtain a working photorefractive sample from a single-component cyclotriphosphazene molecule by a melt/press technique was unsuccessful because of microcracks formed after cooling to room temperature, which we attribute to mechanical stresses from the thermal compression.…”
Section: Photorefractivitymentioning
confidence: 99%
“…Nonlinear optical poling can be performed either by heating in an electric field or by a photoassisted procedure. Photorefractivity has been demonstrated for a series of such homopolymers, [25,26] andÐwhile still not optimalÐit provides the basis for a photonic switching function.…”
Section: Photorefractivesmentioning
confidence: 99%